Learning Azure Cosmos DB : A beginner's guide to creating scalable, globally distributed, and highly responsive applications using Cosmos DB /: A beginner's guide to creating scalable, globally distributed, and highly responsive applications using Cosmos DB. (2018) - Shaikh, Shahid
No abstract available